Hubungan Pemberian ASI Eksklusif Dengan Diare Pada Balita Di Puskesmas Kesugihan I - Suyanto, Murdiyani; Purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
Diarrhea is one of the gastrointestinal infections that poses a global health problem. In 2022, there were 93 cases (15.7%) of diarrhea in toddlers treated in the service area of Puskesmas (Community Healthcare Center) Kesugihan I. Promotive and preventive efforts, such as exclusive breastfeeding, aim to reduce diarrhea in toddlers.To analyze the correlation between exclusive breastfeeding and the incidence of diarrhea in toddlers in the service area of Puskesmas Kesugihan I. This study is a non-experimental comparative quantitative research with a retrospective case-control approach. Secondary data collection techniques from the MTBS poly visit register book, daily PISP Puskesmas register, EPPGBM data and baby cohort. Based on the Chi-square test results, exclusive breastfeeding is significantly associated with the incidence of diarrhea in toddlers, with a p-value of 0.001 (p 0.05). Therefore, toddlers who are not exclusively breastfed have a 3.631 times higher risk of experiencing diarrhea compared to those who are exclusively breastfed (p = 0.001, OR = 3.631, CI = 1.915-6.886. The results of this study indicate the importance of exclusive breastfeeding as an ideal nutritional provision to protect children from various diseases, including diarrhea. Health education efforts on the importance of exclusive breastfeeding, prevention and early management of diarrhea in infants, as well as support for mothers during the exclusive breastfeeding period and until the child is 2 years old during breastfeeding and complementary feeding, are necessary.